AUSTRALIA’S HEDGING STRATEGY IN THE UNITED STATES-CHINA RIVALRY IN THE INDO-PACIFIC REGION 2018-2022 - Ernianda, Annisa; Patriani, Ira; Halunaza, Hardi (Intermestic: Journal of International Studies, 2025)
Indo-Pacific region has been an important region for Australia, Australia has made Indo-Pacific as a main region for implementing its foreign policy. Indo-Pacific region is known as high politic economic region with the influential countries, this become both a strength and a weakness for Australia. Though Australia get advantages to join important cooperation, US-China rivalry conflict requires a bad impact for Australia. Political conflict makes the stability of Indo-Pacific region begins to fall, so Australia trying to control its national security. Australia must choose an impartial policy between the US-China, though Australia has diplomatic relations with both. This research uses descriptive qualitative research, with Hedging Theory and Balance of Power (BOP) Theory. The results of this study elucidated the hedging strategy implemented by Australia in response to the rivalry conflict between the United States andChina in the Indo-Pacific region during 2018–2022, which posed threats to both Australia's security and regional stability.